Association of cognitive function with Neurofilament light chain in the aqueous humor of human eye - Bai, Jianhao; Wan, Zhongqi; Wang, Minli; Wu, Xue; Wang, Tianyu; Zhang, Yuanyuan; Xue, Yawen; Xu, Hong; Peng, Qing (Frontiers in Aging Neuroscience, 2022)
Objectives To evaluate the predictive clinical role of neurofilament light chain (NfL), amyloid-β (Aβ), glial fibrillary acidic protein (GFAP), and phosphorylated tau at threonine 181 (p-tau181) proteins in human aqueous humor (AH) and quantify the retinal macular microvascular parameters by optical coherence tomography angiography (OCTA) as early diagnostic markers of Alzheimer’s disease (AD). Methods This prospective, single-site, cross-sectional, cohort study enrolled 55 participants, including 38 patients with neovascular age-related macular degeneration (nAMD) and 17 individuals with senile cataracts. The single-molecule array platform was used to quantitatively measure the levels of AH NfL, Aβ40, Aβ42, GFAP, and p-tau181 proteins in AH. The mini-mental state examination (MMSE) score was used to assess the global cognitive function. OCTA scan with 6 × 6 mm macular area was used to quantify the retinal thickness and microvascular densities of superficial retinal capillary plexuses and deep retinal capillary plexuses. Results NfL, Aβ40, Aβ42, GFAP, and p-tau181 were detected in all AH samples by Simoa platform. Individuals with cataract had higher concentrations of NfL and p-tau181 but lower Aβ40 and Aβ42 and similar GFAP compared to those with nAMD. Lower MMSE scores showed a negative correlation with NfL concentration of AH not only in the nAMD group (p = 0.043), but also in the cataract group (p = 0.032). However, the MMSE scores were not associated with the levels of Aβ40, Aβ42, GFAP, or p-Tau181. Further analysis found that the Aβ40 and Aβ42 concentrations showed a strong positive correlation (p < 0.0001). In addition, the NfL concentration showed a mild positive correlation with that of GFAP in the cataract group (p = 0.021). Although it has not reached statistical significance, there was a correlation between the levels of NfL and Aβ42 in the nAMD group (p = 0.051). Moreover, the macular superficial vessel density values had a negative correlation with the concentration of NfL (p = 0.004) but a positive correlation with MMSE scores (p = 0.045). The macular deep vessel density values were negatively correlated with the concentration of p-tau181 (p = 0.031) and positively correlated with MMSE scores (p = 0.020). Conclusion The examination of AD-related biomarkers in human AH and OCTA may improve the ocular-based AD detection methods and contribute to forestalling the progression of preclinical AD.